New frontiers in the neuropsychopharmacology of mental illness - Laurence Lanfumey (Frontiers Research Topics, 2015)
In recent years, mental illnesses have become recognized as a huge emotional and financial burden to the individual, their relatives and society at large. Stress-related and mood disorders as well as psychoactive substance abuse are among the disorders associated with most disability in high income countries. Suicide, which is often attributed to some underlying mental disorders, is a leading cause of death among teenagers and young adults. At the same time, mental disorders pose some of the toughest challenges in neuroscience research. There are many different categories of mental disorder as defined and classified by the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) and the International Statistical Classification of Diseases 10th Revision (ICD-10). Despite the ongoing improvements of those widely used manuals, the validity and reliability of their diagnoses remain a constant debate. However, it has now become accepted by the scientific community that mental disorders can arise from multiple sources. In that regard, both clinical and animal studies looking at gene-environment interactions have helped to better understand the mechanisms involved in the pathophysiology as well as the discovery of treatments for mental disorders. This Research Topic aims to cover recent progress in research studying how genetic make-up and environmental factors (such as stress paradigm or pharmacological treatment) can contribute to the development of mental disorders such as anxiety, depression, and schizophrenia. This Research Topic also seeks to highlight studies looking at affective-like disorders following the intake of drugs of abuse. We also welcome all research articles, review papers, brief communications, and commentary on topics related to the broad field of Neuropsychopharmacology.